Maintenance or loss of dialect Andalusian features: Internal and external factors - Villena-Ponsoda, Juan Andrés (My University, 2016)
In the last sixty years a steadily maintained process of convergence towards the Castilian national standard has been occurring in Southern Spain affecting urban middle-class speakers’ varieties, particularly phonology and lexis. As a consequence, unmarked features characterising innovative southern pronunciation have become less frequent and, at the same time, certain standard marked features have been adapted to the southern phonemic inventory. Then, urban middle-class varieties have progressively been stretching out the distance separating them from working-class and rural varieties, and bringing them closer to central Castilian varieties. Intermediate, yet incipient koineised varieties have been described including also transitional Murcia and Extremadura dialects (Hernández & Villena 2009, Villena, Vida & von Essen 2015). (1) Some of the standard phonologically marked features have spread out among southern speakers exclusively based on their mainstream social prestige and producing not only changes in obstruent phoneme inventory –i.e. acquisition of /s/ vs. /θ/ contrast, but also standstill and even reversion of old consonant push- or pull-chain shifts –e.g. /h/ or /d/ fortition, affricate /ʧ/, etc. as well as traditional lexis shift (Villena et al. 2016). Internal (grammar and word frequency) and external (stratification, network and style) factors constraining those features follow similar patterns in the Andalusian speech communities analysed so far (Granada, Malaga) but when we zoom in on central varieties, which are closer to the national standard and then more conservative, differences in frequency increase and conflict sites emerge. (2) Unmarked ‘natural’ phonological features characterising southern dialects, particularly deletion of syllable-final consonant, do not keep pace with this trend of convergence towards the standard. Thus a combination of southern innovative syllable-final and standard conservative onset-consonant features coexist. (3). The main idea is that this intermediate variety is formed through changes suggesting that Andalusian speakers look for the best way of accepting marked prestige features without altering coherence within their inventory. Either reorganisation of the innovative phonemic system in such a way that it may include Castilian and standard /s/ vs. /θ/ contrast or re-syllabification of aspirated /s/ before dental stop are excellent examples of how and why linguistic features are able to integrate intermediate varieties between the dialect-standard continuum.
Keywords: Sociolingüística; Español - Aspectos sociales; Variación lingüística; Español de Andalucía